WASTE RECOVERY IN ALGERIA BETWEEN A ROCK AND A RESCUE - Rofia Abada (International Journal of Innovative Technologies in Social Science, 2024)
Since the year 2000, Algeria has been committed to improving the quality of the environment and enhancing the quality of life for its citizens. Efforts have been made to achieve efficient, integrated waste management. The fact is that we are facing a major shock, and for some years now, the state has been showing shortcomings in the field, which demonstrates that the resources deployed need to be strengthened and consolidated. To cushion this shock, we need to come to the rescue with solutions and proposals. This work aims to propose efficient solutions that involve users in waste collection and sorting. To achieve this, we first need to understand the behavior of users by measuring the waste generated and collected, because the majority of citizens want to sort waste, but in reality, this is still not respected.